Q: How do you solve -6y 3x equals 12?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3x + 6y = 12 Rearranging terms: 6y = -3x + 12 Divide through by 6: y = -1/2*x + 2

It is a straight line. standard form is y = mx + b where m = slope 3x - 6y = 12 6y = 3x -12 y = .5x -2 any other line with slope = 0.5 would be parallel to it

3x-6y=9 -3x -3x -6y=9-3x __ ____ -6 -6 y=9-3x ____ -6

6y = 3x + 4

3x-6y=-8

Related questions

y-3x+6y=12 7y=3x+12 y=3x/7 +12/7

3x + 6y = 12 Rearranging terms: 6y = -3x + 12 Divide through by 6: y = -1/2*x + 2

[ y = -12 ] is.

It is a straight line. standard form is y = mx + b where m = slope 3x - 6y = 12 6y = 3x -12 y = .5x -2 any other line with slope = 0.5 would be parallel to it

3x-6y=12; subtract 12 & add 6y to both sides 3x-12=6y; divide by 6 (1/2)x-2=y; re-write y=(1/2)x-2 slope intercept form

3x-6y=9 -3x -3x -6y=9-3x __ ____ -6 -6 y=9-3x ____ -6

6y = 3x + 4

3x-6y=-8

What is 3x-6y=12

3x + 6y = 363x - 6y = 0 add both equations6x = 36x = 63x - 6y = 03(6) - 6y = 018 - 6y = 018 = 6y3 = yThe solution point is (6, 3).

x = 6 and y = -2

5x2y = 3x - 6y 5x2y + 6y = 3x y(5x2 + 6) = 3x y = (3x)/(5x2 + 6) This is a rational function.